2001
DOI: 10.1128/jb.183.22.6676-6683.2001
|View full text |Cite|
|
Sign up to set email alerts
|

The Global Posttranscriptional Regulator RsmA Modulates Production of Virulence Determinants and N- Acylhomoserine Lactones in Pseudomonas aeruginosa

Abstract: Posttranscriptional control is known to contribute to the regulation of secondary metabolism and virulence determinants in certain gram-negative bacteria. Here we report the isolation of a Pseudomonas aeruginosa gene which encodes a global translational regulatory protein, RsmA (regulator of secondary metabolites). Overexpression of rsmA resulted in a substantial reduction in the levels of extracellular products, including protease, elastase, and staphylolytic (LasA protease) activity as well as the PA-IL lect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
232
1
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 323 publications
(241 citation statements)
references
References 36 publications
7
232
1
1
Order By: Relevance
“…The hcnA gene encodes part of the hydrogen cyanide synthase enzyme that is implicated in virulence (44,45). RsmA was shown to previously negatively affect a leader fusion using the tac promoter and the ribosome-binding site region of hcnA (45).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hcnA gene encodes part of the hydrogen cyanide synthase enzyme that is implicated in virulence (44,45). RsmA was shown to previously negatively affect a leader fusion using the tac promoter and the ribosome-binding site region of hcnA (45).…”
Section: Resultsmentioning
confidence: 99%
“…RsmA was shown to previously negatively affect a leader fusion using the tac promoter and the ribosome-binding site region of hcnA (45). An hcnA leader fusion was constructed by annealing 33 nucleotides, including one of the predicted RsmA-binding sites, the ribosome-binding site, and the translational start codon of hcnA.…”
Section: Resultsmentioning
confidence: 99%
“…The retarding effect of RsmA on P. aeruginosa is demonstrated in Figure 4A of Pessi et al [21], whereby the up regulation of QS activity is initiated significantly earlier in a rsmA − mutant than in the wild-type. Chugani et al [6] observed similar results in their experiments comparing wild-type and qscR − strains; however, the repressive action of qscR is currently uncertain.…”
Section: Background Inhibition (Bi)mentioning
confidence: 89%
“…Discoveries in recent years have shown that a few species have evolved means of bypassing this problem, by repressing certain components of the QS process. The most well studied examples are those of P. aeruginosa [6,7,8,21] and A. tumefaciens [4,23]. The repression mechanisms investigated in this paper are summarised below, the first two being known to be relevant for P. aeruginosa and the last to A. tumefaciens.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation